The Green Banking Operations and Their Role In Achieving Sustainable Banking Performance In Babil Governorate - Noor Hashim Mohammed; Hamid Mohsin Jadah (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2025)
Introduction to The Problem: The concept of green banking has gained significant importance. Green banking operations refer to banking practices focused on environmental sustainability and social responsibility. These practices not only benefit the environment but also have a positive influence on overall sustainable banking performance. Purpose: This study aims to examine the nature of green banking operations and their impact on banking performance. Design/Methodology/Approach: A quantitative study was conducted using a structured questionnaire distributed to a sample of customers of three banks in Hilla city (Baghdad, National Bank of Iraq, and International Development Bank) during the period from April 15 to May 15, 2025. 100 questionnaires were distributed, and 10 were excluded for incompleteness, leaving 90 questionnaires valid for statistical analysis. Design/Methodology/Approach: A quantitative research method was employed, utilizing a structured questionnaire distributed over a 30-days period (15 April 2025 - 15 May 2025). The study targeted commercial banks operating in Babil Governorate, specifically the Hilla branch. A Likert‑scale questionnaire was distributed across these banks, with a total of 100 questionnaires handed out. Of these, 90 valid responses were analyzed, while 10 were excluded due to invalidity. Findings: Present the article’s results indicate that adopting green banking practices such as energy conservation, paper reduction, digital banking systems, and financing environmentally positive projects directly enhances operational efficiency, lowers costs, boosts customer satisfaction, and, ultimately, improves the overall performance indicators of the banking institution